Estrogen Biosynthesis and Signal Transduction in Ovarian Disease - Xu, Xue-Ling; Huang, Zheng-Yuan; Yu, Kun; Li, Jun; Fu, Xiang-Wei; Deng, Shou-Long (Frontiers in Endocrinology, 2022)
Estrogen mainly binds to estrogen receptors (ERs) to regulate menstrual cycles and reproduction. The expression of ERalpha (ERα), ERbeta (ERβ), and G-protein-coupled estrogen receptor (GPER) mRNA could be detected in ovary, suggesting that they play an important role in estrogen signal transduction in ovary. And many studies have revealed that abnormal expression of estrogen and its receptors is closely related to ovarian disease or malignant tumors. With the continuous development and research of animal models, tissue-specific roles of both ERα and ERβ have been demonstrated in animals, which enable people to have a deeper understanding of the potential role of ER in regulating female reproductive diseases. Nevertheless, our current understanding of ERs expression and function in ovarian disease is, however, incomplete. To elucidate the biological mechanism behind ERs in the ovary, this review will focus on the role of ERα and ERβ in polycystic ovary syndrome (PCOS), ovarian cancer and premature ovarian failure (POF) and discuss the major challenges of existing therapies to provide a reference for the treatment of estrogen target tissue ovarian diseases.